Optimization of enzymatic hydrolysis of tilapia (Oreochromis niloticus) by-product using response surface methodology - Roslan, Jumardi; Mustapa Kamal, Siti Mazlina; Md. Yunos, Khairul Faezah; Abdullah, Norhafizah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Fish protein hydrolysate was recovered from tilapia by-product (TB) through enzymatic hydrolysis using alcalase enzyme. Hydrolysis reaction of TB was monitored according to the degree of hydrolysis (DH) by employing O-phtaldialdehyde (OPA) method. Optimization process for obtaining high yield of TB protein hydrolysate was performed using response surface methodology (RSM) by optimizing a combination of four independent variables namely, pH (6.5-8.5), temperature (55-70°C), substrate concentration (10-17.5% w/v), and enzyme concentration (1.5-3.5% w/w) with (DH) as a response. The optimum enzymatic hydrolysis conditions were obtained at pH 7.5, temperature of 60°C, substrate concentration of 15% (w/v) and 2.5% (w/w) of enzyme concentration and yielded about 20.20% of DH after hydrolyzing for 120 min. RSM generated model predicted that 20.42% of DH could be achieved at these conditions and this model was valid based on the DH value obtained from the experimental study (20.31%) which was quite similar with the predicted value. High yield of DH obtained from the optimization process could produce fish protein hydrolysate with good nutritional and functional properties.